The Influence of Health Education About Detection of Maternal Emergencies on the Motivation of Pregnant Women in Doing Antenatal Care (ANC) - Ririn Ratnasari; Fetty Rosyadia; Sri Andayani (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2023)
Emergencies are events that are unexpected or occur suddenly, are often dangerous events. The way to prevent emergencies is to do good planning, follow good guidelines and carry out continuous monitoring of the mother/client. This study aims to determine the effect of health education about early detection of maternal emergencies on the motivation of pregnant women to perform antenatal care. This type of research used a pre-experimental research design type of one group pre-test post-test, with a cross sectional approach. The population in the study were all pregnant women with a sample of 30 respondents taken by total sampling technique. Data collection obtained from primary data. Primary data obtained by filling out questionnaires by respondents. processing data using spearman rank analysis with the SPSS method. The results of the tabulation and data processing stated that there was an increase in the motivation of pregnant women to carry out ANC as an effort to prevent maternal emergencies through health education. Evidenced by the results of data processing, from 30 respondents before receiving health counseling pregnant women had